2012
DOI: 10.1073/pnas.1210659109
|View full text |Cite
|
Sign up to set email alerts
|

AAA ATPase p97/VCP is essential for TRIM21-mediated virus neutralization

Abstract: Tripartite motif-containing 21 (TRIM21) is a cytosolic IgG receptor that mediates intracellular virus neutralization by antibody. TRIM21 targets virions for destruction in the proteasome, but it is unclear how a substrate as large as a viral capsid is degraded. Here, we identify the ATPase p97/valosin-containing protein (VCP), an enzyme with segregase and unfoldase activity, as a key player in this process. Depletion or catalytic inhibition of VCP prevents capsid degradation and reduces neutralization. VCP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 38 publications
6
88
1
Order By: Relevance
“…TRIM21 localizes to antibody-coated viruses that have invaded the cytosol and targets them for degradation in a process that is dependent upon the proteasome and the AAA ATPase VCP (3,4). Consistent with this mechanism, we observe higher viremia in T21 −/− than T21 +/+ mice in all our in vivo experiments.…”
Section: Resultssupporting
confidence: 76%
“…TRIM21 localizes to antibody-coated viruses that have invaded the cytosol and targets them for degradation in a process that is dependent upon the proteasome and the AAA ATPase VCP (3,4). Consistent with this mechanism, we observe higher viremia in T21 −/− than T21 +/+ mice in all our in vivo experiments.…”
Section: Resultssupporting
confidence: 76%
“…Importantly, we observed that the inhibition of tau aggregation was more dependent on VCP than the proteasome. This is in contrast to adenovirus neutralization, in which proteasome and VCP activities are equally critical (1,5). VCP has been linked to both proteasomal degradation and autophagy; however, we did not observe any reduction in the neutralization of aggregation under conditions where autophagy was prevented.…”
Section: Discussioncontrasting
confidence: 53%
“…After binding to antibody, TRIM21 triggers a potent neutralization response that inhibits viral infection. Neutralization of infection is accompanied by degradation of viral components, which requires the activity of the proteasome and the molecular unfoldase, valosincontaining protein (VCP) or p97 (1,5). Detection of viruses and bacteria by TRIM21 does not rely on microbial PAMPs, as model substrates such as antibody-coated latex beads can be bound and detected by TRIM21 (1,3).…”
mentioning
confidence: 99%
“…Many TRIM proteins (there are ∼100 members in humans) have reported roles in innate immunity (1). TRIM21 intercepts incoming, cytoplasmic antibody-coated pathogens and neutralizes them by mediating their VCP-and proteasome-dependent degradation (2,3). In addition, TRIM21 initiates a signaling cascade, resulting in the transcriptional up-regulation of inflammatory cytokines and a potent antiviral state in surrounding cells (4).…”
mentioning
confidence: 99%